The Sopranos. Seasons 5-6, Part one [videorecording (Blu-Ray)] - Chase, David, 1945 August 22-; Chase, David, 1945 August 22-; Grey, Brad, 1957-2017; Gandolfini, James; Bracco, Lorraine, 1955-; Falco, Edie; Imperioli, Michael, 1966-; Chianese, Dominic, 1931-; Pastore, Vincent; Van Zandt, Steve; Sirico, Tony; Iler, Robert, 1985-; et al. (HBO Home Entertainment, 2020)
Tony Soprano is in a mob family that is falling apart. He also has troubles with his wife and children. To help make sense of this, he is seeing a psychiatrist and taking Prozac.